Financial Reporting Procedure at Badan Pengelola Keuangan dan Aset Daerah (BPKAD) Cilegon - Prasadhita, Chandra; Nawawi, Muhammad; Barnia, Rifanti (Management Science Research Journal, 2023)
The purpose of this study was to determine the application of accounting in financial reporting procedures at BPKAD Cilegon. There are several obstacles in the process of preparing financial statements. Using a descriptive method, the authors conducted interviews directly with accounting staff at BPKAD Cilegon. Secondary data was also obtained by the author from several sources related to research. The results of the study show that the financial reports of BPKAD Cilegon are guided by Government Accounting Standards (SAP), Government Regulation Number 71 of 2010, and Government Regulation Number 12 of 2019. Simral is an integrated information system starting from planning, budgeting and financial management at BPKAD Cilegon.